Analisis Quality Control pada Pesawat MRI 1,5 Tesla di Instalasi Radiologi Rsud Bali Mandara - Putri Wirya Febriyani; I Made Lana Prasetya; I Putu Surya Dharma Negara (KOLONI, 2026)
Magnetic Resonance Imaging (MRI) is a diagnostic imaging modality with a high capability to produce optimal soft tissue contrast. The quality of MRI images is strongly influenced by system performance; therefore, routine quality control (QC) is essential to maintain consistency and reliability of imaging results. This study aims to analyze the implementation of QC on a 1.5 Tesla MRI system through artifact evaluation and the application of a visual checklist at the Radiology Installation of RSUD Bali Mandara.This study employed a qualitative design with a survey approach. Data were collected through direct observation of MRI QC procedures, implementation of a visual checklist, and artifact evaluation using a water phantom. Scanning was performed using T1-weighted axial and T2-weighted axial sequences with standard parameters. The results showed that MRI QC procedures were conducted routinely through daily and weekly assessments. The visual checklist evaluation indicated that the MRI system was generally in good condition. Artifact evaluation revealed no artifacts in the phantom images. Environmental parameters, including room temperature (20.33°C), humidity (59.7%), and helium level (93.8%), were within stable and acceptable ranges. In conclusion, the implementation of MRI QC has been carried out effectively through a combination of artifact evaluation and visual checklist. This approach can serve as a practical method for maintaining MRI image quality and supporting reliable diagnostic outcomes in radiology services.